Percutaneous Coronary Intervention Literature Review - Tona, Azwar Iwan (CoinReads Media Prima, 2024)
This literature review examines the advancements and outcomes associated with Percutaneous Coronary Intervention (PCI), a minimally invasive procedure widely utilized to treat coronary artery disease. The review highlights key studies that evaluate the efficacy and safety of PCI, comparing it to traditional surgical options such as coronary artery bypass grafting (CABG). It explores the evolution of PCI techniques, including drug-eluting stents and optical coherence tomography, and their impact on patient outcomes, including rates of restenosis and major adverse cardiovascular events. Stents should be deployed to attain minimal residual stenosis, referred to as optimum stenting. The achievement of a substantial luminal diameter reduces the likelihood of stent thrombosis and restenosis. Patients receiving elective stent therapy are often discharged within 24 hours post-implantation, following overnight observation and monitoring. Same-day discharge may be suitable for elective patients who have an easy operation and possess a minimal risk of post-discharge complications.